2012
DOI: 10.1158/1078-0432.ccr-11-2381
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Effect of the Dual-Targeting Strategy Involving PI3K/AKT/mTOR and RAS/MEK/ERK Pathways in Patients with Advanced Cancer

Abstract: Purpose: This study evaluated the clinical relevance of the dual-targeting strategy involving PI3K/AKT/ mTOR and RAF/MEK/ERK pathways.Experimental Design: We investigated safety, efficacy, and correlations between tumor genetic alterations and clinical benefit in 236 patients with advanced cancers treated with phase I study drugs targeting phosphoinositide 3-kinase (PI3K) and/or mitogen-activated protein kinase (MAPK) pathways in our Phase I Clinical Trials Program.Results: Seventy-six (32.2%) patients receive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
310
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(326 citation statements)
references
References 25 publications
14
310
2
Order By: Relevance
“…The clinical impact of such a parallel pathway blockade remains unclear, but none of the 11 patients treated with PI3K pathway inhibitors plus MEK inhibitors in our series had benefit in terms of response or disease stabilization. A recently published large data set reported similarly disappointing results, with no partial responses or disease stabilizations for more than 16 weeks in 16 patients with metastatic colorectal cancers treated using the same approach (43).…”
Section: Discussionmentioning
confidence: 97%
“…The clinical impact of such a parallel pathway blockade remains unclear, but none of the 11 patients treated with PI3K pathway inhibitors plus MEK inhibitors in our series had benefit in terms of response or disease stabilization. A recently published large data set reported similarly disappointing results, with no partial responses or disease stabilizations for more than 16 weeks in 16 patients with metastatic colorectal cancers treated using the same approach (43).…”
Section: Discussionmentioning
confidence: 97%
“…It was reported that p-EGFR level was much higher in 4T1 tumors than in cell cultures, suggesting potential crosstalk with exogenous growth factors and cytokines in the in vivo tumor environment and that combinatorial targeting of FGFR and EGFR might be advantageous (38,82). Although combination therapy with selective inhibitors is possible when available, rationally designed dual and multitargeted inhibitors have the potential advantage of possessing the desired polypharmacology engineered into a single compound, thereby avoiding potential drug-drug interactions that can arise with combination treatment (83). Dual covalent inhibitors of EGFR and VEGFR have been designed previously, but these compounds possessed two electrophilic groups.…”
Section: Discussionmentioning
confidence: 99%
“…The study also suggested that the combination may be synergistic in different genomic backgrounds and can block the multiple cyclinD1-and CDK4-activating mechanisms for inhibited growth and proliferation of PI3Ki resistant cells. Simultaneous co-inhibition of RAS/RAF/MAPK and PI3K/AKT/mTOR pathways has emerged as a popular scheme for combination therapy [108][109][110]. Targeting these two pathways may be particularly effective in cancers attributed to mutations in PI3K and either KRAS or BRAF [108].…”
Section: Simultaneously Targeting Major Oncogenic Pathways By Multiplmentioning
confidence: 99%
“…Simultaneous co-inhibition of RAS/RAF/MAPK and PI3K/AKT/mTOR pathways has emerged as a popular scheme for combination therapy [108][109][110]. Targeting these two pathways may be particularly effective in cancers attributed to mutations in PI3K and either KRAS or BRAF [108]. In ovarian clear cell carcinoma, inhibition of a downstream target of mTOR and HIF-1 activated the RAS pathway via MEK phosphorylation, and combination therapy using inhibitors of MEK and mTOR simultaneously synergistically eradicated HIF-1α-silenced cells [111].…”
Section: Simultaneously Targeting Major Oncogenic Pathways By Multiplmentioning
confidence: 99%